Platforma 2 Zbornik študentk in študentov Podiplomske šole ZRC SAZU - Kuhar, Lea; Zalar, Vita (ZRC SAZU, Založba ZRC, 2020)
Platforma 2 is a scientific publication in which the students of the Postgraduate school ZRC SAZU present their completed and ongoing research. The edited volume combines contributions from various fields of humanities and social sciences, arising from a wide range of research topics.